If tan^3 theta -4√3.tan theta +3=0, then: tan theta =?

Question

If tan^3 theta -4√3.tan theta +3=0, then: tan theta =?

in progress 0
Raelynn 2 months 2021-10-10T18:10:11+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-10T18:12:02+00:00

    Step-by-step explanation:

    Tan theta =. a/b

    height/base= a/ b

    therefore, height= a

    base= b

    by Pythagoras theorem

    hypotenuse square = sum of square of other sides

    let hypotenuse be ” c”

    c square = a square+ b square

    therefore, c=the whole square root of a square +b square

    sec theta = hypotenuse/base

    = the whole square root of a square +b square/ b

    hope it helps you mate

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )